The Common Monetary Area in Southern Africa : Shocks, Adjustment, and Policy Challenges - Masha, Iyabo (IMF Working Papers; Working Paper ;, 2007)
This study assesses the experience of the Common Monetary Area (CMA) based on available empirical evidence over the last two decades. It pays particular attention to member countries' adjustment to economic shocks in recent years and the inter-country linkages, including the spillover effects of policies. The paper draws the main lessons from the CMA experience, identifies key policy challenges, and discusses the issues facing the member countries in their efforts to achieve sustained growth. Implications for further economic integration in a broader regional context are also noted.